Peran Guru Pendidikan Agama Islam Dalam Penerapan Kurikulum Merdeka di SMK Bina Patria 2 Sukoharjo - Miftaqul Hayat Destya Putra Tama; Edy Muslimin; Yunan Hidayat (Departement of Mathematics Education, 2023)
This research aims to describe the role of Islamic religious education teachers in implementing an independent learning curriculum in class X to improve student understanding at SMK Bina Patria 2 Sukoharjo District while forming good character in students. The research method uses descriptive qualitative research methods. This research was conducted because it saw the phenomenon at SMK Bina Patria 2 Sukoharjo, where many students' understanding still needed to be more superficial in understanding learning material. The research instrument used an interview guide. Through the results of interviews conducted with Islamic religious education teachers at SMK Bina Patria 2 Sukoharjo District that seventh-grade students use their curriculum this study Islamic religious education teachers focus more on developing self-potential, as well as being able to increase the understanding of students concerned with their potential. So it can be concluded that students are students who are subjects in the world of education who have the potential to gain knowledge from a teacher as a provision for someone to face the challenges of the times, become a society that has a prominent personality, and become a whole human being in Islam. Teachers automatically play an essential role in implementing an independent curriculum, both subject teachers and other teachers are necessary for the Islamic religious education teacher.